Edukasi Terhadap Remaja untuk Meningkatkan Minat Berinvestasi - Yahya Nusa; Daniel Nemba Dambe; Nely Salu Padang; Natalia Reyne Lumenta; Spedy Paereng (STIE Jambatan Bulan, 2023)
The development and progress of the times requires each generation to continue to adjust and learn about it, for example about investing.The purpose of this community service activity is to educate teenagers who are still in high school to know about investment. This activity took place at SMK Katolik Tunas Bangsa. Education about the meaning, purpose, benefits, impact and how to make an investment. After carrying out this activity, the youth of the Tunas Bangsa Catholic Vocational School were very satisfied because this activity was able to provide a good understanding of investment and how to make good and safe investments, as well as assisting youth in starting investment studies starting from opening a stock account through the Poems Id application Keywords: Investment,